DOWN TO EARTH – Circular Materials Flows & Resource Salvation - exploring the use of excavated earth material from Västlänken, focusing on Rammed Earth techniques in a Nordic urban context. - Matsdotter, Vera (My University, 2020)
Architects around the world have finally declared a climate and biodiversity emergency as the most serious issue of our time. This is no longer an abstract threat; it is real. From now on, our buildings, cities and infrastructure must become self-sustaining systems. And this all begins with our use of material. Future architects bear the responsibility to study the evidence relating to natural bio-based fossil free materials and techniques that can be incorporated in circular flows. Radical tectonics must be explored, where waste is considered as a material resource. Massive amounts of earth from excavations can be found in urban areas, from the construction of infrastructure projects (tunnels, metros, parking garages etc.). Earth, the clay-mixed material beneath our feet, has already been shaped into buildings lasting hundreds of years. This master’s thesis will focus on the potential use of Construction Demolition Waste (CDW) material; specifically local earth masses excavated from the Västlänken metro in Gothenburg. The scalability of the rammed earth techniques in colder climates will be examined, making a case for clay as a future circular building material in a Nordic urban context. The design section of the thesis will be a proposal for one of the stations for the new metro. The methodology will involve using the case study as an example of a design-for-material approach. It is important to showcase the potential of local waste material in the urban environment. Compacted earth, like stone, is heavy and slow to change with the passage of time. It might not be renewable, but is completely recyclable and with a minimal CO2 footprint. Like concrete, earth can be controlled to respond to a variety of sites and desired forms – in other words, it might well be an architect’s dream material. The aesthetics of rammed earth are striking, but the story behind the material is even more powerful